2023
DOI: 10.1002/ffj.3745
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing key aroma‐active compounds of stewed mutton using gas chromatography‐olfactometry‐mass spectrometry coupled with odour activity value

Abstract: Stewed mutton is popular for its nutritional and special flavour qualities. To determine the key aroma‐active compounds of stewed mutton in different parts, six experimental groups (sheep fat, sheep bone, sheep brisket, sheep loin, sheep rib and sheep leg) were investigated by gas chromatography‐olfactometry‐mass spectrometry (GC‐O‐MS). Totally, 57 volatile compounds in mutton soup were identified. Of these, 22 aroma‐active compounds were identified as key aroma compounds with odour activity values (OAVs) >1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Sun et al confirmed that eugenol, linalool, hexanal, anethole, diallyl disulfide, 2-octyl acetate, a-copanen, and 1-octen-3-ol were the key odorants in the storage of cooked beef meatballs by flavor dilution factor and OAV values [ 28 ]. Qi et al detected 57 volatiles by gas chromatography–olfactometry–mass spectrometry (GC-O-MS) and identified 22 odor-active compounds with OAVs more than 1 as key aroma flavor substances in mutton soup [ 29 ]. Jiang et al indicated that 19 key aroma active substances (OAV ≥ 1) had a great influence on salt-roasted chicken legs using GC-MS and OAV analysis, including (E,E)-2,4-heptadienal, ethyl cinnamate,1-octen-3-ol, furfural, octyl aldehyde, trans-2-nonenal, nonyl aldehyde, (E,E)-2,4-nonadienal, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al confirmed that eugenol, linalool, hexanal, anethole, diallyl disulfide, 2-octyl acetate, a-copanen, and 1-octen-3-ol were the key odorants in the storage of cooked beef meatballs by flavor dilution factor and OAV values [ 28 ]. Qi et al detected 57 volatiles by gas chromatography–olfactometry–mass spectrometry (GC-O-MS) and identified 22 odor-active compounds with OAVs more than 1 as key aroma flavor substances in mutton soup [ 29 ]. Jiang et al indicated that 19 key aroma active substances (OAV ≥ 1) had a great influence on salt-roasted chicken legs using GC-MS and OAV analysis, including (E,E)-2,4-heptadienal, ethyl cinnamate,1-octen-3-ol, furfural, octyl aldehyde, trans-2-nonenal, nonyl aldehyde, (E,E)-2,4-nonadienal, etc.…”
Section: Introductionmentioning
confidence: 99%